(untitled) (Revista Contexto & Saúde, 2022)
The study aimed was to identify the QOL of patients with gastrointestinal cancer and chronic pain and to characterize sociodemographic data, clinical, therapeutic and pain graduation, associating them with QOL domains. This is a transversal, quantitative study carried out with patients with gastrointestinal cancer and chronic pain participated in an oncologic gastroenterology outpatient clinic of a general hospital in the city of São Paulo, Brazil. The tools employed were: sociodemographic and clinical questionnaire, the EORTC -QLQC30 instrument and the Brief Pain Inventory (BPI). The data was submitted to descriptive analysis, absolute frequencies and percentages, and analytical, seeking to correlate the domains of QOL, Pain, Performance Status (PS) of patients, using the Spearman correlation coefficient. To compare the domains of the QLQ-C30 and BPI scales with the variables of interest, we used the T-Test. Thirteen patients, mostly male, married, religious, economic classification C2 (61.5%) participated in the study. All were in pain at the time of data collection, with a mean of 2.54 (SD = 2.88) by BPI and the worst reported score in the last 24 hours at 8.15 (SD = 2.03). In addition to pain, the main QOL changes were: fatigue, insomnia and loss of appetite, and the more advanced the disease, the worse the symptoms and functional impairment. The data showed that patients live with pain of moderate intensity and, if worse clinical condition, greater intensity. Pain compromises the quality of life of these patients in multiple aspects, showing that measures need to be taken to favor pain control, from the therapeutic drug regimen to educational and care activities.